Insight into Nrf2: a bibliometric and visual analysis from 2000 to 2022 - Ma, Yawei; Wang, Zhongqing; Hu, Yuedong (Frontiers in Genetics, 2023)
Background: Nrf2 plays a pivotal role in governing the antioxidant defense system, triggering the transcription of diverse genes involved in cellular protection. Its role in mitigating oxidative damage and modulating inflammatory processes has made Nrf2 an attractive target for therapeutic interventions. Despite the growing interest in Nrf2 research, a bibliometric analysis is relatively rare. This study aimed to clarify Nrf2’s role in multiple diseases, identify emerging trends and hotspots using bibliometric analysis, and provide valuable insights and potential directions for future therapeutic interventions. Methods: The Science Citation Index of Web of Science Core library from 2000 to 2022 was searched on 22 October 2022. Use Microsoft Excel, CiteSpace, Bibliometrix, and VOS viewers for data collection and visualization of research focus and trends. Results: A vast collection of 22,040 research studies on Nrf2 published between 2000 and 2022 were identified. Nrf2 research has seen significant growth globally from 2000 to 2022. China leaded in publication numbers (9,623, 43.66%), while the United States dominated in citation frequency with 261,776 citations. China Medical University was the most productive institutions (459, 2.08%). Masayuki Yamamoto topped in publications (307), while Itoh K. ranked first in citations with 3669. Free Radical Biology and Medicine was the journal with the most studies and citations on Nrf2 (613, 29,687 citations). The analysis of keyword clustering enhanced the categorization of topics and can be summarized as oxidative stress, cancer, disorders in glycolipid metabolism, inflammation, and neurological conditions. Conclusion: China and the United States are the pioneers in Nrf2 research. Recently, there has been a comprehensive exploration of Nrf2 involving both experimental and clinical aspects, as well as mechanisms and therapeutic applications. Investigating novel molecular mechanisms, including NF-κB, Ho1, and Keap1, and developing enhanced, targeted Nrf2 activators or inhibitors to uncover the interplay among cancer, glycolipid metabolic disorder, inflammation, and neurological disorders will be upcoming trends and hotspots.